Pengembangan Sistem Manajemen Perizinan Angkutan Umum berbasis Web (Studi Kasus: Bidang Angkutan Jalan Dinas Perhubungan Kota Malang) - Firdaus Yulia Fika Maulidya; Denny Sagita Rusdianto; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Licensing is one of the mandatory document requirements for public transport to operate. The application for licensing permits at the Malang City Transportation Service is carried out by means of the transportation driver submitting the required documents at the Malang City Transportation Service. This method results in delays in transportation work because they have to apply for permits which are time-consuming. In addition, the request for a permit due to incomplete documents experienced by the Malang City Transportation Service caused the licensing process to take a long time. A web-based general permit management system was developed to be able to provide a solution to this problem. The system was developed using the waterfall software development model and the approach used is object-oriented. The system testing uses 3 strategies, namely unit test, integration test, and validation test. Unit and integration tests use white box testing, while validation tests use black box testing. The results of the white box testing with 3 test cases showed valid results, while the results of the black box testing with the test of 67 functional requirements showed valid results.